Implementation of green building principle for residential building / Wan Nurfaizzatun Wan Salleh - Wan Salleh, Wan Nurfaizzatun (Faculty of Architecture, Planning and Surveying, 2015)
Green building is a design, construction and maintenance techniques and practices that can reduce the environmental impact of a building such as air quality, consumer health, natural resources, land use, water quality and energy consumption. The KLIA 2 will target to achieve LEED Gold and GBI Gold/Platinum awards, seeking to reduce the consumption of energy by at least 50%, the use of portable water reduced by 50% and waste to landfill by 60%. This research was conducted to identify the green building principle and determine the principles of green building compliance or not in the residential building. The opinion and views of related parties in the residential areas were obtained from questionnaire and observation in case studies which have been identified to give a clearer picture of the current situation of the green residential building in Malaysia. Based on the findings, it was concluded that the residential areas in Malaysia, not really familiar with the green building principle and only several residential areas was compliance the green building principle.